Aerodynamics And Performance Of Variable Pitch Vertical Axis Turbines At Low Tip Speed Ratios - Suresh Raj, Aaron Basil Raj (Universiti Sains Malaysia, 2021)
The shift to renewable energy is imminent to aid the reduce its total carbon footprint and fight off global warming. Wind and hydrokinetic energy have great potential to replace the depleting reserves of fossil fuels. With its scalability and omnidirectional advantage, vertical-axis turbines are a great renewable energy source for off-grid and rural areas. Although the vertical characteristics of the turbine look promising, it is known to have far lower performance than its horizontal counterpart. This research investigates the detailed aerodynamic study of lift and drag contribution on the turbine blades with variablepitch blade through numerical simulation via an open-source software called Qblade. The problems to be investigated in this research are the effects of pitch angle on the aerodynamic contribution of the blades and the variable-pitch model to improve performance over various operating ranges. It is suggested that applying pitch angle to the blade at a controlled amount can help maintain a constant steady angle of attack, which can be altered to extract the most performance. The effects of blade pitching would be studied to determine the instantaneous aerodynamic loadings, the tangential and normal forces while ultimately referencing the average power coefficient, for overall performance. Variable-pitch blade will be employed in this study to compare and determine the benefit and drawback of the pitching method for vertical-axis turbine performance. The investigation would be carried out by a series of numerical simulations of a single-bladed Darrieus turbine in Qblade using the Lifting Line Free Vortex Wake (LLT) module. A single blade is chosen to solely study the complete aerodynamic loading without compromising the effects of multiple blades and complex wakes. The blade Blade Designer module with a NACA 0018 airfoil profile and experimentally tested extrapolated airfoil polar data to ensure realistic and accurate data. Validation studies are then carried out by comparing the simulated results from Qblade to Computational Fluid Dynamics (CFD) solution and experimental tests to ensure the method and model used in the simulation are accurate and trustworthy. The data obtained from Qblade is then processed in MATLAB to observe the aerodynamic loads on the blade and the aerodynamic contribution to the power produced in a turbine rotation. A fine-tuned variable-pitch blade will be created through MATLAB and implemented via Simulation Input Files in a turbine model in Qblade. LLT simulation would be carried out for low tip-speed ratios of 0.75, 1.0, 1.6, 2.0, and 2.5, allowing us to observe the impact of different tip-speed ratios on variable-pitch blade.